Research on the Curriculum Construction of Innovation and Entrepreneurship Education in Independent Colleges - Xie, Jun (Journal of Theory and Practice of Contemporary Education, 2024)
It is imperative for independent colleges to promote the construction and reform of innovation and entrepreneurship education curriculum. We should adhere to the principles of overall optimization, coordination between theory and practice, systematization and dynamic adjustment. The main way of construction is to lay equal stress on theory and practice, and to cultivate the application ability of ft; Curriculum modularization, offering courses for industry and society; Strengthen the construction of curriculum and teaching materials; Integrate internal and external resources and strengthen the construction of curriculum practice teaching conditions. he theory of "embodied cognition" emerged in the 20th century, mainly due to the dilemma of mind-body dualism, and is regarded as the second generation cognitive revolution. "Embodied cognition" advocates that cognition arises from the interaction between the body and the environment, and that the mind, body and environment are closely linked as a unified whole. It emphasizes that "there is no mind without a body", focuses on the participation of the body in cognitive activities, emphasizes the dynamic interaction between the body and the environment, and encourages multi-sensory participation in experience. The practical nature of music is one of the essential properties of music, and the learning of music, such as singing, playing, appreciating, and creating, is inseparable from physical participation. The rise of "embodied cognition" provides a new perspective and new ideas for music education.